Gerakan Sehat Bersama: Pemeriksaan Gula Darah Untuk Menunjang 9 Pilar Transformasi Kesehatan - Digna Renny Panduwati; Suryani M. F Situmeang; Nita Andriani Lubis; Sri Widia Ningsih; Wardati Humaira (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2024)
Diabetes is a chronic disease characterized by high body sugar levels, but the body does not utilize them. Based on data from 2023, 14% of Indonesia's population has diabetes. The spread of diabetes also penetrates rural areas, posing a threat to rural areas and threatening the health of rural communities, and Saentis Village is no exception. The program "Healthy Movement Together: Blood Sugar Checking to Support the 9 Pillars of Health Transformation" is a community service initiative that aims to increase public health awareness. Some people in Saentis Village have a history of diabetes. This activity aims to provide education and conduct initial screening for diabetes. The service method is carried out by collaborating between medical personnel, local government, and the community. The activity began by providing education about the dangers and early symptoms of diabetes and continued by conducting an initial diabetes screening by checking blood sugar. Ninety-six people attended this activity. Based on the results of the examination, it was found that as many as 17 people had high blood sugar levels, and as many as 14 people experienced hyperglycemia. Based on the results of the screening that has been carried out, it is known that there are people who are not aware of the importance of maintaining a lifestyle, so there are still 14.6% of people who have pre-diabetes conditions, so it is necessary to check HbA1C.